THE ECCLESIOLOGICAL IMPLICATION OF THE TRINITY AS DIVINE COMMUNION AND LOVE (Hekima Review, 2023)
Missiologists like David Bosch, Steve Bevans, and Roger Schroeder suggest that the Trinity is the foundation not only for the nature of the Church but also for its mission, both ad intra and ad extra. In other words, they see the mission Dei as the key missiological paradigm. In so doing, they establish an intrinsic relationship between the Church and the Trinity that must be considered. This link between the mystery of the Trinity and ecclesial life makes it possible to conceive the Church as a participant in Trinitarian life, “an icon of the Trinity.” If this is the case, the Church’s mission is participation in the mission of the Trinity, and it can only fulfil this mission if the communion and love that characterize the Trinity are also lived in the Church. The article, therefore, argues in favour of a Trinitarian ecclesiology of communion that establishes a correlation between intra-trinitarian perichoresis and the life of the Church, emphasizing unity in diversity.